Anti-Hepatoma Compound Determination by the Method of Spectrum Effect Relationship, Component Knock-Out, and UPLC-MS2 in Scheflera heptaphylla (L.)Frodin Harms and Its Mechanism - Liu, Xuqiang; Jiang, Nan; Xu, Xiaoqing; Liu, Cunyu; Liu, Zhenhua; Zhang, Yan; Kang, Wenyi (Frontiers in Pharmacology, 2020)
Scheflera heptaphylla (L.)Frodin, a kind of Traditional Chinese Medicine, is commonly used in anti-inflammatory, analgesic, anti-viral, anti-tumor, and hemostasis. This study aimed to determine the anti-hepatoma components and its mechanism from the leaves of S. heptaphylla. The spectrum-effect relationships were analyzed by the method of Partial least squares, indicating that P1, P2, and P10 were positively correlated to inhibitory activity of Huh7 cells. Whereas others were negatively correlated. The technologies of component knock-out and UPLC-MS2 were used to determine compounds as 3,4-Dicaffeoylquinic acid (P6), 3,5-Dicaffeoylquinic acid (P7), 3α-Hydroxy-lup-20(29)-ene-23,28-dioic acid (P10, named Compound A). The results forecasted that Compound A had the best correlation with inhibitory activity. The effects of Compound A on the activities of human hepatoma cells (Huh7, SMMC-7721, HepG 2) and normal hepatocytes (L0-2, Chang liver) were evaluated. Cell apoptosis was observed with inverted microscope and flow cytometer. In addition, the proteins, related to apoptosis, were detected by Western blot. The results showed that Compound A (400 nM) could significantly inhibit the activity of three hepatoma cells (P < 0.001) with slight toxicity to normal hepatocytes, and the IC50 values were 285.3 and 315.1 nM, respectively, which were consistent with the prediction of spectrum-effect relationships. After treatment with Compound A, the number of hepatoma cells decreased significantly. And the apoptosis rate of Huh7 cells increased significantly (P < 0.001) in Compound A (200, 400 nM) groups, SMMC-7721 and HepG 2 were directly necrotic. Compound A groups could significantly improve the level of intracellular reactive oxygen species (ROS) (P < 0.05, P < 0.001) in Huh7 with no effect on normal hepatocytes. The content of apoptotic protein (Bax and Bim) in mitochondria was significantly increased in Compound A groups (P < 0.001). On the contrary, the content of anti-apoptotic protein (Bcl-xL and Mcl-1) decreased significantly (P < 0.001). These results demonstrated that Compound A was the main anti-hepatoma active component in the S. heptaphylla leaves. It achieved the effect of promoting apoptosis of Huh7 cells by regulating the levels of ROS and Bcl-2 family protein in mitochondrial apoptosis pathway.